ClOOCl photolysis at high solar zenith angles: analysis of the RECONCILE self-match flight - Suminska-Ebersoldt, O.; Lehmann, R.; Volk, C. M.; Borrmann, S.; Rex, M.; Stroh, F.; von Hobe, M.; Wegner, T.; Grooß, J.-U.; Hösen, E.; Weigel, R.; Frey, W.; et al. (Atmospheric Chemistry and Physics, 2012)
The photolysis rate constant of dichlorine peroxide (ClOOCl, ClO dimer) J(ClOOCl) is a critical parameter in catalytic cycles destroying ozone (O-3) in the polar stratosphere. In the atmospherically relevant wavelength region (lambda > 310 nm), significant discrepancies between laboratory measurements of ClOOCl absorption cross sections and spectra cause a large uncertainty in J(ClOOCl). Previous investigations of the consistency of published JClOOCl with atmospheric observations of chlorine monoxide (ClO) and ClOOCl have focused on the photochemical equilibrium between ClOOCl formation and photolysis, and thus could only constrain the ratio of J(ClOOCl) over the ClOOCl formation rate constant k(rec). Here, we constrain the atmospherically effective J(ClOOCl) independent of k(rec), using ClO measured in the same air masses before and directly after sunrise during an aircraft flight that was part of the RECONCILE field campaign in the winter 2010 from Kiruna, Sweden. Over sunrise, when the ClO/ClOOCl system comes out of thermal equilibrium and the influence of the ClO recombination reaction is negligible, the increase in ClO concentrations is significantly faster than expected from J(ClOOCl) based on the absorption spectrum proposed by Pope et al. (2007), but does not warrant cross sections larger than recently published values by Papanastasiou et al. (2009). In particular, the existence of a significant ClOOCl absorption band longwards of 420 nm is not supported by our observations. The observed night-time ClO would not be consistent with a ClO/ClOOCl thermal equilibrium constant significantly higher than the one proposed by Plenge et al. (2005).